Subunit architecture of intact protein complexes from mass spectrometry and homology modeling - Taverner, Thomas; Devos, Damien; Russell, Robert B. (Accounts of chemical research, 2008)
Proteomic studies have yielded detailed lists of protein components. Relatively little is known, however, of interactions between proteins or of their spatial arrangement. To bridge this gap, we are developing a mass spectrometry approach based on intact protein complexes. By studying intact complexes, we show that we are able to not only determine the stoichiometry of all subunits present but also deduce interaction maps and topological arrangements of subunits. To construct an interaction network, we use tandem mass spectrometry to define peripheral subunits and partial denaturation in solution to generate series of subcomplexes. These subcomplexes are subsequently assigned using tandem mass spectrometry. To facilitate this assignment process, we have developed an iterative search algorithm (SUMMIT) to both assign protein subcomplexes and generate protein interaction networks. This software package not only allows us to construct the subunit architecture of protein assemblies but also allows us to explore the limitations and potential of our approach. Using series of hypothetical complexes, generated at random from protein assemblies containing between six and fourteen subunits, we highlight the significance of tandem mass spectrometry for defining subunits present. We also demonstrate the importance of pairwise interactions and the optimal numbers of subcomplexes required to assign networks with up to fourteen subunits. To illustrate application of our approach, we describe the overall architecture of two endogenous protein assemblies isolated from yeast at natural expression levels, the 19S proteasome lid and the RNA exosome. In constructing our models, we did not consider previous electron microscopy images but rather deduced the subunit architecture from series of subcomplexes and our network algorithm. The results show that the proteasome lid complex consists of a bicluster with two tetrameric lobes. The exosome lid, by contrast, is a six-membered ring with three additional bridging subunits that confer stability to the ring and with a large subunit located at the base. Significantly, by combining data from MS and homology modeling, we were able to construct an atomic model of the yeast exosome. In summary, the architectural and atomic models of both protein complexes described here have been produced in advance of high-resolution structural data and as such provide an initial model for testing hypotheses and planning future experiments. In the case of the yeast exosome, the atomic model is validated by comparison with the atomic structure from X-ray diffraction of crystals of the reconstituted human exosome, which is homologous to that of the yeast. Overall therefore this mass spectrometry and homology modeling approach has given significant insight into the structure of two previously intractable protein complexes and as such has broad application in structural biology.